A Prospective Randomized Clinical Trial of a Novel, Noninvasive Perfusion Enhancement System for the Prevention of Hospital-Acquired Sacral Pressure Injuries. Issue 4 (July 2018) - Bharucha, Jitendra B.; Seaman, Linda; Powers, Michele; Kelly, Erica; Seaman, Rodney; Forcier, Lea; McGinnis, Janice; Nodiff, Isabel; Pawlak, Brooke; Snyder, Samantha; Nodiff, Susan; Patel, Rohan; et al.
Abstract : PURPOSE: The purpose of this study was to determine the effectiveness of a novel, noninvasive perfusion enhancement system versus beds with integrated alternating pressure capabilities for the prevention of hospital-acquired sacral region (sacral, coccygeal, and ischium) pressure injuries in a high-risk, acute care patient population. DESIGN: A prospective randomized trial of high-risk inpatients without preexisting sacral region pressure injuries was conducted. SUBJECTS AND SETTING: The sample comprised 431 randomly enrolled adult patients in a 300-bed tertiary care community teaching hospital. METHODS: Subjects were randomly allocated to one of 2 groups: control and experimental. Both groups received "standard-of-care" pressure injury prevention measures per hospital policy, and both were placed on alternating pressure beds during their hospital stays. In addition, patients in the experimental group used a noninvasive perfusion enhancement system placed on top of their alternating pressure beds and recovery chairs throughout their hospital stay. Fischer's exact probability test was used to compare group differences, and odds ratio (OR) were calculated for comparing pressure injury rates in the experimental and control groups. RESULTS: Three hundred ninety-nine patients completed the trial; 186 patients were allocated to the experimental group and 213 patients to the control group. Eleven patients in the control group versus 2 in the experimental group developed hospital-acquired sacral region pressure injuries (51.6% vs 1.07%; P = .024). Control patients were 5.04 times more likely to develop hospital-acquired sacral region pressure injuries (OR = 0.1996; 95% CI, 0.0437-0.9125). CONCLUSIONS: Patients using a noninvasive perfusion enhancement system developed significantly fewer hospital-acquired sacral pressure injuries than those using an alternating pressure bed without the perfusion enhancement system. These findings suggest that a perfusion enhancement system enhances the success of use of pressure redistributing beds for prevention of hospital-acquired sacral pressure injuries.